2009
DOI: 10.1097/hp.0b013e3181ad8018
|View full text |Cite
|
Sign up to set email alerts
|

Radon and Leukemia in the Danish Study: Another Source of Dose

Abstract: An epidemiologic study of childhood leukemia in Denmark (2,400 cases; 6,697 controls) from 1968 to 1994 suggested a weak, but statistically significant, association of residential radon exposure and acute childhood lymphoblastic leukemia (ALL). The Danish study estimated a relative risk (RR) = 1.56 (95% CI, 1.05-2.30) for a cumulative exposure of 1,000 Bq m-3 y. For an exposure duration of 10 y their RR corresponds to a radon concentration of 100 Bq m-3. There are two dose pathways of interest where alpha part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…For example, progenitor cells in the less exposed neighborhood of the investigated part of the epithelium can support the maintenance of cell count by proliferating and migrating into the highly exposed area. Furthermore, stem cells from bone marrow possibly present in the bronchial epithelium (Harley and Robbins 2009;Massberg et al 2007) can also help tissue maintenance.…”
Section: Area Ratio (%)mentioning
confidence: 99%
“…For example, progenitor cells in the less exposed neighborhood of the investigated part of the epithelium can support the maintenance of cell count by proliferating and migrating into the highly exposed area. Furthermore, stem cells from bone marrow possibly present in the bronchial epithelium (Harley and Robbins 2009;Massberg et al 2007) can also help tissue maintenance.…”
Section: Area Ratio (%)mentioning
confidence: 99%
“…Whole-body γ-ray doses have been found to significantly increase risks of leukemia in survivors of atomic bombings in Japan (Hsu et al, 2013), risks of leukemia, NHL and MM in the U.K. radiation workers (Muirhead et al, 2009), and risks of leukemia and NHL in Chornobyl cleanup workers (Kesminiene et al, 2008; Zablotska et al, 2013). Less is known about the effects of radon decay alpha particles on the bone marrow, but a recent study (Harley and Robbins, 2009) reported that the bronchial mucosa has an abundance of circulating lymphocytes, thus suggesting that RDP exposures could be associated with hematologic cancers originating from these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Results from previous studies on the possible effect of exposure of indoor radon on risk of childhood leukemia have been largely negative but still inconclusive. The potential dose pathway for the association, in addition to the exposure of the red bone marrow, has been suggested to be through the exposure of lymphocytes within the tracheobronchial epithelium (23). Studies in Norway, France, the UK, and Switzerland showed no association, but a Danish case-control study with complete residential histories and a statistical model with 40% r 2 reported an elevated risk (24)(25)(26)(27)(28).…”
Section: Health Effects Of Indoor Radonmentioning
confidence: 99%